Dengue na região dos Vales do Taquari e Rio Pardo - RS? - Flávia Pereira Bavaresco; Beanir Silva Lara; Janete Aparecida Alves Machado; Eliane Carlosso Krummenauer; Marcelo Carneiro (Universidade de Santa Cruz do Sul, 2012)
.